Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Solve for $x$ the equation $\arccos(2x)-\arccos(x)=\pi/3$.

My attempt using $\cos(a-b)$. But it gives me a sqrt-expression that I don't know how to handle.

WolframAlpha

share|improve this question
add comment

3 Answers

up vote 1 down vote accepted

This reduces to an easy quadratic. First, take the cosine of both sides. Using the cosine addition formula, I get

$$2 x \cdot x + \sqrt{1-4 x^2} \sqrt{1-x^2} = \frac12$$

Manipulate and square both sides to get

$$\left ( 2 x^2-\frac12\right)^2 = (1-4 x^2)(1-x^2) = 1-5 x^2+4 x^4$$

or

$$3 x^2=\frac{3}{4} \implies x = \pm \frac{1}{2}$$

Now plugging in both answers, one sees that only the $-1/2$ result makes sense for the principal branch (or any branch) of the arccos. Thus, $x=-1/2$.

share|improve this answer
    
Why is it only x=-1/2 that satisfies the equation? I set up: acos(1) - acos(0.5)= pi/3 and acos(-1) - acos(-0.5)= pi/3 Now I can get multiple results, since acos(1)=pi/2 and also =3pi/4. How should I think about that? –  jacob Sep 29 '13 at 11:58
    
@jacob: $\arccos{1}=0$, $\arccos{(1/2)}=\pi/3$. –  Ron Gordon Sep 29 '13 at 12:24
add comment

Hint: $\arccos\left(2x\right)=\arccos\left(x\right)+\pi/3$. Now take the cosinus on both sides and see what happens.

share|improve this answer
add comment

Avoid squaring which often incurs the burden of extraneous roots

Let $\displaystyle \arccos x=\theta\ \ \ \ (1)\implies x=\cos\theta$

We have $\displaystyle \arccos(2\cos\theta)-\theta=\frac\pi3\implies \arccos(2\cos\theta)=\theta+\frac\pi3\ \ \ \ (2) $

As the principal value of $\arccos$ lies $\in[0,\pi],$

from $(1), 0\le\theta\le\pi$

form $(2), 0\le\theta+\frac\pi3\le\pi\implies -\frac\pi3\le\theta\le\frac{2\pi}3$

So, we need $\displaystyle 0\le \theta\le \frac{2\pi}3\ \ \ \ (3)$

$\displaystyle (2)\implies 2\cos\theta=\cos\left(\frac\pi3+\theta\right)=\cos\frac\pi3\cos\theta-\sin\frac\pi3\sin\theta$

$\displaystyle \implies\frac{\sqrt3}2\sin\theta=\left(\frac12-2\right)\cos\theta$

$\displaystyle \implies\tan\theta=-\sqrt3=\tan\left(-\frac\pi3\right)$

$\displaystyle \implies \theta=n\pi-\frac\pi3$ where $n$ is any integer

From $\displaystyle(3), 0\le n\pi-\frac\pi3\le \frac{2\pi}3\iff 0\le3n-1\le2\implies n=1$

Can you take it from here?

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.